High risk of postoperative complications in dialysis patients undergoing total hip arthroplasty: a database study of Japanese nationwide medical claims - Hidetatsu Tanaka; Kunio Tarasawa; Yu Mori; Kazuyoshi Baba; Hideki Fukuchi; Kiyohide Fushimi; Kenji Fujimori; Toshimi Aizawa (Scientific Reports)
Abstract Dialysis patients who develop degenerative hip disease or femoral neck fractures may require total hip arthroplasty, and their comorbidities predispose them to complications. This study aimed to evaluate whether dialysis was associated with early postoperative complications using a large database of Japanese. In this cohort study, using the Japanese National Administrative Diagnosis Procedure Combination database on THA for patients on hemodialysis or not from December 2011 to March 2023, we assessed the surgical-related complications, medical complications, and mortality during hospitalization after propensity score matching by age, sex, BMI, and comorbidities. A total of 2,111 pairs of patients on hemodialysis and non-dialysis were included. In THA for patients on hemodialysis, the significant odds ratios for various complications were as follows: dislocation (2.616, 95% CI: 1.282 to 5.338, p < 0.01), reoperation (2.104, 95% CI: 1.222 to 3.623, p < 0.01), deep vein thrombosis (0.407, 95% CI: 0.286 to 0.579, p < 0.01), cerebrovascular events (4.426, 95% CI: 1.495 to 13.10, p < 0.01). These findings help identify postoperative THA risks for patients on dialysis, suggesting that more attention should be paid to preoperative planning and postoperative care.